Hypertension among Mississippi Workers by Sociodemographic Characteristics and Occupation, Behavioral Risk Factor Surveillance System. (17th July 2020) - Mendy, Vincent L.; Vargas, Rodolfo; Ogungbe, Oluwabunmi; Zhang, Lei
Abstract : In 2017, Mississippi had the third highest age-adjusted prevalence of hypertension in the United States. We estimated the prevalence of hypertension by sociodemographic characteristics and occupation and examined the association between hypertension with occupation and sociodemographic characteristics among Mississippi workers. We calculated adjusted prevalence and adjusted prevalence ratios (APRs) by sociodemographic characteristics and occupation among Mississippi adult workers. We analyzed combined 2013, 2015, and 2017 data from the Mississippi Behavioral Risk Factor Surveillance System for 6, 965 workers in ten Standard Occupational Classification System major groups. Of the estimated 1.1 million Mississippi workers during the three survey years, 31.4% (95% confidence interval (CI), 30.0–32.8) had hypertension. The likelihood of having hypertension was significantly higher among workers aged 30–44 years, 45–64 years, blacks, and those classified as overweight and obese workers compared to their counterparts. The likelihood of having hypertension among workers in the fields of installation, repair and maintenance, and production were 26% higher (APR, 1.26; 95% CI, 1.03–1.55) and 33% higher (APR, 1.33; 95% CI, 1.11–1.58), respectively, than workers in all other occupational groups. Among Mississippi workers, hypertension prevalence varied by sociodemographic characteristics and occupational groups. Age, race, obesity status, installation, repair, maintenance, and production occupation groups are associated with an increased likelihood of hypertension. Novel and/or community-based or linked programs are needed that could target workers at risk of hypertension that are outside of a single-site workplace.